“Saying ‘I Do’ All Over Again” - Marc Ouellette (Semiotic Review)
This article details a project that involved collecting the necessary items to produce a set of wedding pictures. While photographs have long been understood as indexical signs, the process of collecting the items via trips to thrift stores reveals a host of additional indexical signs through the set of underlying contextual cultural constraints surrounding the difference between the rituals of the marriage rite and the wedding as a public, performative practice. Indeed, the second hand items leave indexical and material traces of the excess and the disposability of weddings, while the pictures offer the material connection to the ostentation of the event. Ultimately, the pictures and the disposability of the host of single-use items reveal weddings as a kind of packaging, to be discarded after use. Even so, for the witnesses of the event, the pictures offer a material attachment that is sustained in and through their indexicality.